(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Field experiments were conducted for two rainfed seasons(2006 and 2007) and one irrigated season (2008) at the Agricultural Farmof the Upper Nile University in Malakal (Sudan). The objective of theexperiments was to study the effect of each of farmyard manure, waterhyacinth compost, Rhizobium seed inoculation and in dual combinationson groundnut symbiotic performance and growth and yield under bothrainfed and irrigation systems. The organic fertilizers were applied at therate of 15 t ha-1 each. The results showed that each organic manure alonesignificantly increased shoot dry weight, number of nodules plant -1 andpod and hay yields than the control in both rainfed and irrigation systems.Rhizobium seed inoculation with either manure significantly increasedplant shoot and plant root dry weights, plant nodulation, early podformation, absorption of plant N and plant P compared to the control.Moreover, these treatments significantly increased groundnut pod andhay yields over that of the control.